Parental preferences for financial incentives, and other aspects of preschool vaccination pro-grammes: a discrete choice experiment - Flynn, D; Ternent, L; Becker, F; Oluboyede, Y; Adams, J (SAGE Publications, 2017)
Objective: To establish preferences of parents and guardians of preschool children for the organization of preschool vaccination services, including financial incentives. Design: An online discrete choice experiment. Participants: Parents and guardians of preschool children (up to age 5 years) who were (n = 259) and were not (n = 262) classified as at high risk of incompletely vaccinating their children. High risk of incomplete vaccination was defined as any of the following: aged less than 20 years, single parents, living in one of the 20% most deprived areas in England, had a preschool child with a disability, or had more than three children. Main Outcome Measures: Participant preferences expressed as positive (utility) or negative (disutility) on eight attributes and levels describing the organization of preschool vaccination programs. Results: There was no difference in preference for parental financial incentives compared to no incentive in parents "not at high risk" of incomplete vaccination. Parents who were "at high risk" expressed utility for cash incentives. Parents "at high risk" of incomplete vaccination expressed utility for information on the risks and benefits of vaccinations to be provided as numbers rather than charts or pictures. Both groups preferred universally available, rather than targeted, incentives. Utility was identified for shorter waiting times, and there were variable preferences for who delivered vaccinations. Conclusions: Cash incentives for preschool vaccinations in England would be welcomed by parents who are "at high risk" of incompletely vaccinating their children. Further work is required on the optimal mode and form of presenting probabilistic information on vaccination to parents/guardians, including preferences on mandatory vaccination schemes.